Relationship Between Growth Hormone Gene Polymorphism with Milk Production and Its Components in Black Iraqi Goat - Muntaha Y. Yousief; Jaafar M. Owaid; Raghdan H. Mohsin (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2023)
Local black goat are raised for the purpose of milk production. The goal of the current study was to identify the growth hormone gene's single nucleotide polymorphism (SNPS). Additionally, the effect of the GH gene SNP on the milk qualities of Iraqi black goat was evaluated.  DNA was extracted from blood samples of 28 goat. A segment with a length of 330 bp in the third intron and the fourth exon of the GH gene was analyzed. Bioinformatics software was used to analyze the results. The results showed the presence of three genotypes (TT, TC, CC) at position 263 of the studied plot with a frequency of 0.36, 0.21, and 0.43, respectively. The local breed was characterized by a decrease in observed heterozygosity (21.43%). However, the expected heterozygosity was 50.65%. Low heterozygosity may indicate the presence of inbreeding within the same herd. Haplotypes network revealed a genetic relationship between the local Iraqi goat and the Egyptian goat. As well as the existence of a genetic relationship at a lower level with the Indian goats. From Tajima's D test and Fu's Fs (1.547 and 1.428), the results led to a rise in inbreeding. In milk production, energy, and the amounts of protein. The analysis of the data using bioinformatics tools predicted the effects of identified the genotypes in which the amino acid was not altered, and this is where the mutation was found. There is a relationship between the genetic polymorphism of the growth hormone gene and the production of milk and its components. The CC genotype was superior in milk production, energy, and the amounts of protein and fat over the TC and CC combinations.